TENDENCIES AND INNOVATIVE APPROACHES IN LANGUAGE LEARNING IN THE ERA OF GLOBAL DIGITALIZATION - Taiteliyeva M.A, Taiteliyeva M.A; Bayetova A.S , Bayetova A.S (Журнал иностранных языков и лингвистики, 2025)
Today, global digitalization is drastically transforming all spheres of human activity, including the field of education. Language learning, in particular, is undergoing significant changes under the influence of new technologies, leading to the emergence of innovative approaches and new tendencies in the acquisition of foreign languages [1]. One of the main tendencies is the wide implementation of online platforms and applications designed specifically for language learning. Tools such as Duolingo, Memrise, and Babbel offer interactive lessons that adapt to the learner’s level, making the process more personalized and efficient [2]. Additionally, artificial intelligence is increasingly being integrated into educational platforms, offering personalized feedback, error correction, and adaptive learning paths